Skepticism and the skeptical spirit. Stanley Cavell: The philosophical challenge of literature. - Dawe, M. Wanda. (University of Ottawa (Canada), 1998)
This thesis investigates different interpretations of modern skepticism in philosophy and literature. In philosophy, skepticism is most generally understood as the achievement (or consequence) of a certain kind of epistemological enquiry. Whether skepticism is directed toward knowledge of the existence of a separate and independent, "external" world, or toward our knowledge of the existence of others like ourselves in it (in the Anglo-American tradition, what is called "the problem of other minds"), this comprehensive philosophical perspective is most often neither consistently defended nor absolutely refuted and yet it remains a constant theme of contemporary philosophy. But in Shakespearean Tragedy, Romanticism, and American Transcendentalism, skepticism is presented as a moral or practical issue rather than, or at least prior to, any epistemological one that may arise. If the latter view is a defensible one, and this thesis attempts to show that it is, then its consequences for, and beyond, philosophy are as disturbing as they are fascinating. An interpretation of certain key literary texts as studies of skepticism is part of the overall argument of this thesis to the effect that literature challenges philosophy's understanding of the skeptical problem, hence also philosophy's self-understanding. Furthermore, the investigation of certain interactions between philosophy and literature with respect to skepticism undertaken in the present work challenges our ordinary understanding of what it is to think about and to describe ourselves and the world, philosophically or otherwise, and what it is to act, one among others, as a knower and agent in the world.
Keywords: Literature, General.